The superior colliculus is sensitive to gestalt-like stimulus configuration in hemispherectomy patients. (August 2016) - Georgy, Loraine; Celeghin, Alessia; Marzi, Carlo A.; Tamietto, Marco; Ptito, Alain
Abstract: Patients with cortical blindness following a lesion to the primary visual cortex (V1) may retain nonconscious visual abilities (blindsight). One intriguing, though largely unexplored question, is whether nonconscious vision in the blind hemifield of hemianopic patients can be sensitive to higher-order perceptual organization, and which V1-independent structure underlies such effect. To answer this question, we tested two rare hemianopic patients who had undergone hemispherectomy, and in whom the only post-chiasmatic visual structure left intact in the same side of the otherwise damaged hemisphere was the superior colliculus (SC). By using a variant of the redundant target effect (RTE), we presented single dots, patterns composed by the same dots organized in quadruple gestalt-like configurations, or patterns of four dots arranged in random configurations, either singly to the intact visual hemifield or bilaterally to both hemifields. As reported in a number of prior studies on blindsight patients, we found that bilateral stimulation yielded faster reaction times (RTs) than single stimulation of the intact field for all conditions (i.e., there was an implicit RTE). In addition to this effect, both patients showed a further speeding up of RTs when the gestalt-like, but not the random shape, quadruple patterns were projected to their blind hemifield during bilateral stimulation. Because other retino-recipient subcortical and cortical structures in the damaged hemisphere are absent, the SC on the lesioned side seems solely responsible for such an effect. The present results provide initial support to the notion that nonconscious vision might be sensitive to perceptual organization and stimulus configuration through the pivotal contribution of the SC, which can enhance the processing of gestalt-like or structured stimuli over meaningless or randomly assembled ones and translate them into facilitatory motor outputs.